DISTRIBUSI DAN PRODUKTIVITAS TENAGA KERJA PADA USAHATANI KARET (Hevea brassillensis) DI DESA BENTOK DARAT KECAMATAN BATI-BATI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Yayuk Minta Wahyuningsih; Zuraida Zuraida (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
The reaserch was conducted in Bentok Darat village,Bati-Bati district,for sampling the farmers were taken by purpose namely that seck klon pb 260 as much as 16 farmers. Outpouring of labor in the family bigger role that 77,13 % out family that much 22,87 %.The index value in labour productivity of Rp 93.482,58 higher than the wage rate of Rp 40.000,.while for the value of land productivity of 5,8 ton/ha.